Scots and France As Seen through Alba Amicorum, 1540s-1720s - Thomas BROCHARD (E-REA)
The article will study the Scots found in alba amicorum from the 1540s through to the 1720s along socio-professional lines. The relationships developed by these Scottish contributors with the album owners are usually hard to decipher at the personal level within the strict confines of album entries. Yet certain findings emerge to appreciate and delineate the contours of these contacts which evolved according to the identity of these individuals themselves but also their messages, environments, religious persuasions, gender, status, and social interactions to name but a few. The very notion of relating or rather that of friendship, inherent in these livres d’amitié through their name, is stretched to its limits both chronologically speaking and in terms of intensity, dealing with both deep and superficial relationships. The collation of documents seems to be one promising avenue to investigate that nature of the relationships thus formed or cultivated. Actually, the issue of relating within alba seems to be too restrictively construed and needs to be opened up. These album entries firmly ground these Scots within France and its various milieus, whether student, professional, clerical, diplomatic, or scientific and highlight their relations with these environments and activities or professions.